STUDY ON FRY PERFORMANCE OF BLACK TIGER SHRIMP Penaeus monodon WITH SPECIAL REFERENCE TO ITS MORPHOLOGY AND RNA/DNA RATIO ANALYSIS - Haryanti Haryanti; Ketut Mahardika; Sari Budi Moria; I Gusti Ngurah Permana (Indonesian Aquaculture Journal, 2006)
Standard method to asses the performance of black tiger shrimp (Penaeus monodon) fry was needed for successful shrimp culture. The main purpose of this study was to determine standard method fry performance of P. monodon assesment based on its morphology and molecular RNA/DNA ratio analysis. Samples of P. monodon fry were collected from hatcheries in Bali, six hatcheries in East Java, three hatcheries in Central Java and six hatcheries in South Sulawesi. Each hatchery gave 25 appropriate sizes of fry samples taken from same tank culture. RNA/DNA ratio value was obtained from gene-quant measurement.  Result of this study shown that morphology performance of shrimp fry correlated with RNA/DNA ratio.  RNA/DNA ratio of shrimp fry from Bali hatcheries were obtained of 0.7121. Shrimp fry from hatcheries in East Java  showed  RNA/DNA value ranged between 0.2823-1.2132, while shrimp fry from hatcheries in Central Java and South Sulawesi  ranged between 1.1810-17478  and  0.1798-0.5116 respectively.